Human consumption of seaweed and freshwater aquatic plants in ancient Europe - Stephen Buckley; Karen Hardy; Fredrik Hallgren; Lucy Kubiak-Martens; Žydrūnė Miliauskienė; Alison Sheridan; Iwona Sobkowiak-Tabaka; Maria Eulalia Subirà (Nature Communications, 2023)
Abstract During the Mesolithic in Europe, there is widespread evidence for an increase in exploitation of aquatic resources. In contrast, the subsequent Neolithic is characterised by the spread of farming, land ownership, and full sedentism, which lead to the perception of marine resources subsequently representing marginal or famine food or being abandoned altogether even at the furthermost coastal limits of Europe. Here, we examine biomarkers extracted from human dental calculus, using sequential thermal desorption- and pyrolysis-GCMS, to report direct evidence for widespread consumption of seaweed and submerged aquatic and freshwater plants across Europe. Notably, evidence of consumption of these resources extends through the Neolithic transition to farming and into the Early Middle Ages, suggesting that these resources, now rarely eaten in Europe, only became marginal much more recently. Understanding ancient foodstuffs is crucial to reconstructing the past, while a better knowledge of local, forgotten resources is likewise important today.